Beyond the gathering storm [large type] - Oke, Janette, 1935- (Oke, Janette, 1935- Canadian West series, 2012)
"The love of Wynn and Elizabeth Delaney healed their adopted son Henry's painful memories and helped him grow into a man of character. Then his job as a Royal Canadian Mountie brings tragedy into his life once again. Assigned to a new post some five years later, he rediscovers someone who may be able to help him put his past behind him. And when Henry's sister, Christine, leaves home, she finds employment and loses her heart. But is she on the wrong path?"--Publisher